(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ikawati S, Himawan T, Abadi AL, Tarno H. 2020. Thermostability, photostability, and toxicity of clove oil nanoparticles against Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae). Biodiversitas 21: 4764-4771. Problems related to the essential oils as insecticides are their volatility, poor solubility in water and environmental degradation (such as caused by high temperatures and UV light) which can adversely affect the application. An ideal botanical insecticide formulation would maintain the level of the main compounds adequate for pest control. This study was to evaluate the stability of polyethylene glycol (PEG) coated nanoparticles loaded with clove (Syzygium aromaticum) essential oil to high temperature and UV light also their toxicity to C. ferrugineus. There is a reduction in nanoparticle size after heating from 257 to 173 nm and there is no difference in size distribution. After heating and UV-light treatment, eugenol content in free clove oil decreased significantly, while on nanoparticles there were not significantly changed, that indicated greater stability on the nanoformulation. The median lethal concentration (LC50) of CO-NPs to C. ferrugineus adults value for 72 and 120 hours was 0.734 and 0.676%.